Taurine and isolated mitochondria: A concentration-response study - Hamidreza Mohammadi; Mohammad Mehdi Ommati; Omid Farshad; Akram Jamshidzadeh; Mohammad Reza Nikbakht; Hossein Niknahad; Reza Heidari (Shiraz University of Medical Sciences, 2019)
Taurine (TAU) is the most abundant free amino acid in the human body. High concentrations of this amino acid are found in tissues such as the skeletal muscle, brain, and kidney. Recently, a focus has emerged on the effects of TAU on cellular mitochondria. It has been found that TAU could positively affect this organelle by enhancing mitochondrial membrane potential, increasing ATP levels, and mitigating mitochondria-mediated ROS formation. The current study aimed to evaluate the effect of a wide range of TAU concentrations (0.01 mM-1000 mM) on mitochondrial function. Mice liver mitochondria were isolated and exposed to different concentrations of TAU (30 min). Several indices, including mitochondrial depolarization, dehydrogenases activity, permeabilization, and ATP content, were monitored. It was found that TAU supplementation significantly enhanced parameters such as mitochondrial ATP levels and mitochondrial membrane potential in comparison with the control group. Moreover, TAU prevented Ca2+-induced mitochondrial permeabilization. This amino acid revealed no significant adverse effect on isolated mitochondria even at very high and supra-physiological concentrations (e.g., 100, 250, and 500 mM). These data suggest TAU as an ideal and safe agent to protect mitochondria against toxic insults or regulating cellular function in different mitochondria-linked disorders.